Path analytic approach towards demystifying the key triggers behind liking different cricket formats - a Kolkata based study / Subhasis Ray, & Soma Roychowdhury - Ray, Subhasis; Roychowdhury, Soma (Universiti Teknologi MARA, 2022)
Cricket has multiple international formats. This study aims to find out if gender and age have any influences on liking any formats. It delves deep into the outcome quality of a cricket match to build a construct for understanding fans' psyche behind fondness for any formats. The same construct is used to model overall liking for each format. The study uses Chi-square test for independence to investigate the influence of gender and age group on overall liking of a format. It uses Confirmatory Factor Analysis (CFA) to establish the dimensional construct and applies Structural Equation Model (SEM) to model overall liking based on the construct. The study finds no link between gender and liking of a format even though age group appears to influence. It establishes the construct REST comprising of Result, Excitement, Skill, Time and Money to measure overall liking for a format. Result and Skill are found to be insignificant for predicting the liking of Tests and T20 respectively whereas ODI appears to be more balanced. The findings give a clear indication to the regulators that test matches need to be made more unpredictable and result-oriented and T20 matches less restricted and more skilful. The regulators need to strategize making the younger generation interested in test and the older generation in T20. REST can be treated as a pioneering construct that can explain fan's expectation from a game of cricket leading to liking a format.